Pengembangan Media Pembelajaran Interaktif Articulate Storyline Materi Proses Pembentukan Tanah dan Komponen Penyusun Tanah Kelas IX SMP - Maulida, Rabiatul; Sari, Mella Mutika; Istyadji, Maya (CV. ITTC INDONESIA, 2023)
The development of information technology in the digital era certainly has a major influence on the development of the world of education. The existence of the digitalization process makes the delivery of learning materials more leverage. One way to involve digitalization during learning is by using interactive learning media. Describing the validity and practicality of the Articulate Storylin interactive learning media is the aim of this study. The research method used is Research and Development (R&D) with the ADDIE development model (Analyse, Design, Develop, Implement and Evaluate). Validation sheets and student response questionnaire sheets became tools for data collection. Aiken's V validity test and percentage are the methods used in technical data analysis in this study. This study involved 4 experts and 32 students. The result of expert validation is 0.82 while the practicality test result is 83%. Based on these results, it can be concluded that the Articulate Storyline interactive learning media material for soil formation and soil constituent components for class IX SMP can be used in science learning in junior high schools because it has been declared very valid and also very practical.